PELATIHAN KARYA TULIS ILMIAH BAGI SISWA - Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This Community Service (PKM) activity specifically aims to, 1) provide understanding to Senior High School Students regarding tips and tricks for writing Scientific Papers (KTI), 2) improve students' skills in writing KTI, and 3) improve the quality of students' KTI results. The training participants were 30 students of Madrasah Aliyah Tarbiyatut Tholabah. The materials presented during the training included, 1) Basic Concepts of Compiling KTI, 2) Anatomy of KTI, 3) Use of Language in KTI, and 4) Tips and Tricks for Overcoming Plagiarism in KTI. The methods used during the training were lectures, demonstrations, interactive discussions and coaching clinics. The results of this PkM activity were, 1) Students gain basic knowledge about compiling KTI such as papers, articles and proposals, 2) Students are able to compile KTI in accordance with the systematics and writing criteria, and 3) Students are able to write quality KTI